PENGARUH PROFITABILITAS, LEVERAGE, UKURAN PERUSAHAAN DAN CAPITAL INTENSITY TERHADAP TAX AVOIDANCE PADA PERUSAHAAN DI BURSA EFEK INDONESIA - Putra, Tommy Permana; Effendi, Syahril (LPPM Universitas Putera Batam, 2021)
In the world of taxation, there are still cases of tax avoidance committed by some corporate people to minimize tax payments that must be paid by the company in ordered to get even more maximum profits. This study aims to determine the effect of certain variables namely Profitability, Leverage, Company Size and Capital Intensity on Tax Avoidance in property and real estate sub-sector companies listed on the Indonesia Stock Exchange. The population in this study amounted to 61 property and real estate sub-sector companies listed on the Indonesia Stock Exchange in 2015-2019. The sampling technique in this study used a purposive sampling method so that 16 companies were registered that met the criteria in selecting the sample. The data used in this study are secondary data in the form of financial reports obtained from the Indonesia Stock Exchange. The results of the F test produce a significant effect that means Profitability, Leverage, Company Size and Capital Intensity simultaneously affect Tax Avoidance so that the regression model contained in this study is worthy of research. Partially, the t-test presents profitability that significantly affects tax avoidance, while leverage, company size and capital intensity have no significant effect on corporate tax avoidance.